Antimicrobial Stewardship Barriers and Goals in Pediatric Oncology and Bone Marrow Transplantation: A Survey of Antimicrobial Stewardship Practitioners. (7th December 2015) - Wolf, Joshua; Sun, Yilun; Tang, Li; Newland, Jason G.; Gerber, Jeffrey S.; Van Dyke, Christie J.; Hymes, Saul R.; Yu, Diana; Carias, Delia C.; Bryant, Penelope A.
Abstract : We undertook a cross-sectional survey of antimicrobial stewardship clinicians in North America and Australasia regarding practices, goals, and barriers to implementation of stewardship for pediatric oncology patients. Goals and barriers were similar regardless of clinician or institutional characteristics and geographic location. Strategies addressing these factors could help optimize antimicrobial use. Infect. Control Hosp. Epidemiol. 2016;37(3):343–347